QT dispersion in hemodialysis and CAPD patients - TOKAY TARHAN, SENA (KARGER, 2002)
Prolongation of repolarization dispersion (QT interval dispersion) measured from the 12-lead surface ECG has been associated with sudden cardiac death and ventricular tachyarrhythmias in a variety of cardiac disorders. The aim of our study was to assess the effects of hemodialysis (HID) and continuous ambulatory peritoneal dialysis (CAPD) on QT dispersion in end-stage renal disease patients. 20 chronic HID patients (mean age 57.75 +/- 13.79 years) and 20 CAPD patients (mean age 50.79 +/- 14.94 years) who had no complaints and symptoms of cardiac arrhythmias as well as 20 healthy volunteers (mean age 48.74 +/- 10.88 years) underwent ECG testing. All HID patients were on bicarbonate three times weekly with cuprophane capillaries. 12-lead ECGs were recorded on the day after HID. The CAPD patients were on a standard CAPD program (four times daily with 2,000 cm(3) peritoneal fluid). ECGs were recorded when the patients were receiving their regular standard CAPD program. All ECGs were analyzed manually by one observer. There were no statistically significant differences in dialysis duration, blood urea nitrogen, creatinine, sodium, calcium, and parathormone values between the HID and CAPD patients. The serum potassium values were significantly higher in HID patients when compared to CAPD patients. There was no difference in the mean of maximal QT among all three groups. The rate of QT interval dispersions was significantly higher in HID and CAPD patients as compared with healthy controls (p < 0.05). There was no statistically significant difference in the QT dispersion rates between HID and CAPD patients. In conclusion, there is a tendency to cardiac arrhythmias in HID patients during the postdialysis period. Although CAPD patients are receiving dialysis daily, they also have higher rates of QT dispersions and accordingly a tendency to arrhythmias. Copyright (C) 2002 S. Karger AG, Basel.
Keywords: QT dispersion; hemodialysis; continuous ambulatory peritoneal dialysis; MAINTENANCE HEMODIALYSIS; CARDIAC-ARRHYTHMIAS